Research progress in drought-tolerant crop screening and intelligent cultivation: Multi-omics and algorithm-driven approaches - Jianliang Bi; Hongpeng Du (Resources Data Journal, 2025)
Against the backdrop of escalating global climate change and increasing water scarcity, enhancing crop drought resistance and resource use efficiency has become a critical pathway toward ensuring food security and promoting sustainable agriculture. This review systematically summarizes recent advances in drought-tolerant crop screening and optimized cultivation strategies, with a focus on five key areas: (1) multi-omics integration for elucidating drought resistance mechanisms; (2) machine learning-based intelligent screening of drought-tolerant varieties; (3) optimization of root system architecture and mechanisms for efficient water utilization; (4) crop-environment dynamic management platforms driven by digital twin technology; and (5) agroecological coupling models for drought-resilient cultivation. This work aims to provide theoretical foundations and technical pathways for crop genetic improvement and the construction of intelligent agricultural systems in drought-prone regions, offering strategic insights for the future development of efficient, resilient, and environmentally friendly drought-adaptive agriculture.